Legal Certainty and Protection of Heirs’ Rights over Digital Assets: Reconstruction of Islamic Inheritance Law in the Digitalization Era - Rachmawan, Farhan; Hidayah, Astika Nurul (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
Digital assets such as cryptocurrency, social media accounts, NFTs (Non-Fungible Tokens), and other types of virtual ownership have emerged as a result of rapid technological advances. This phenomenon raises new issues in Islamic inheritance law in Indonesia, particularly regarding the status, inheritance procedures, and security of assets. This research method uses a normative juridical approach with a legislative and conceptual approach. The study utilizes primary legal sources from legislation, hadith, and the Quran, as well as secondary legal sources from literature reviews. The objective of this research is to evaluate the status of digital assets as inheritable property from an Islamic legal perspective and to determine their legal certainty within the Islamic inheritance system in Indonesia. The results of the study indicate that digital assets, which have economic value, can be inherited according to Islamic law. Highlighting the absence of regulations, technical challenges in access and security, and the need for harmonization between Sharia law and technological developments, despite the detailed regulation of principles of justice and transparency in Islamic inheritance law, the implementation of digital asset distribution is still hindered by the absence of clear legal mechanisms and operational standards for the inheritance of digital assets. To achieve justice and avoid disputes among heirs, there is a need to strengthen regulations, promote Sharia digital literacy education, and foster collaboration between the government, religious scholars, and technology practitioners.